Functional properties of hard kombucha brewed with deep ocean water using Lachancea thermotolerans - Hayeong Kim; Kibeom Jin; Ji Yeon Lee; Tae-hui Yang; Sejin Oh; Soochul Park; Gia-Buu Tran; Huong Thuy Le; Kunal Pal; Ghahyun Jeffrey Kim; Doman Kim (Scientific Reports)
Abstract Hard kombucha is an alcoholic beverage produced by the fermentation of a 40% (v/v) kombucha solution with selected yeast strains and sugar. Among 35 yeast strains examined, Lachancea thermotolerans, known for its high ethanol production, was selected to prepare hard kombucha using tap and deep ocean water. After 21 days of fermentation, the pH of the filtered tap water hard kombucha (TWHK) and deep ocean water hard kombucha (DOWHK) decreased to 2.6–2.69. In contrast, their titratable acidity (TA) increased to 93.68 g acetic acid/L and 107.73 g acetic acid/L, respectively. The ethanol content reached 3.87% alcohol by volume (ABV) in TWHK and 3.92% in DOWHK. DOWHK produced higher levels of organic acids compared with TWHK. Analysis of volatile compounds revealed a shift toward fruity and sweet flavors, with no noticeable off-flavors. Additionally, sensory analysis using an electronic tongue sensor system revealed that DOWHK exhibited greater sourness, astringency, umami, and saltiness than TWHK. Both beverages showed similar antimicrobial activities against Staphylococcus aureus, Escherichia coli, Helicobacter pylori, and Salmonella spp. However, DOWHK suppressed α-glucosidase activity 1.63 times more effectively than TWHK. This study supports the use of deep ocean water in the development of functional fermented beverages for industrial applications.